Structura distribuției indicatorilor de calitate a vieții - Zamfir, Cătălin (Calitatea Vieții, 2021)
In this article, I propose a methodology for interpreting subjective indicators on the topic of quality of life, using several data sets: International Indicators Database (1970), Perceived Quality of Life in Romania (1979), Quality of Life Diagnosis in Romania (1990−2010); Eurobarometer in the EU (2015). The Absolute Data Assessment Scheme (SEDA) is used to interpret subjective data regarding the quality of life. In the first part, I present a short history of the concept of happiness and scientific research regarding quality of life scholarship. In the second part, I present the sociological perspective on the quality of life, focusing on analyzing subjective indicators of quality of life, and explaining the structure of the Absolute data assessment scheme − SEDA.